Ethnography in education - Mills, David 1969-; Morton, Missy; British Educational Research Association (Los Angeles SAGE, 2013)
The title will introduce you to ethnographic "classics", the best existing textbooks, and debates about new approaches and innovations. With extended examples of ethnographic analysis by both established scholars and research students, the authors aim to help you cultivate an "ethnographic imagination" in your own research and writing.
Introduction : schooling the imagination -- Reading ethnography, writing ethnography -- Ethnography by design, ethnography by accident -- Into the educational 'field' : relationships, reciprocities and responsibilities -- Being, seeing, writing : the role of fieldnotes -- New times, new ethnographies? -- What do I do now? : making ethnographic meaning -- Ethnography that makes a difference -- Writing again : communicating ethnographic insights -- Conclusion : being an everyday ethnographer.
Keywords: Educational anthropology -- Research